Using ear molding to correct auricular helix adhesion deformity - Chen, Lili; Li, Chenlong; He, Aijuan; Chen, Ying; Tong, Hua; Fu, Yaoyao; Zhang, Tianyu (Frontiers in Pediatrics, 2022)
Objectives: This study examined the effectiveness of Byrd’s EarWell system for the treatment of auricular helix adhesion. Methods: The newborns with helix adhesion were treated with ear molding. The photos of pinna were taken before, during, and after the treatment. The immediate and long-term outcomes, as well as the complications, were assessed by two independent plastic surgeons. Study design: A retrospective study. Data on family history, neonatal weight, gestational age, delivery method, laterality, gender, age of initiating treatment, medical comorbidities, duration of treatment, and follow-up time were collected. Study site and period: From 2019 to 2021, infants treated with the EarWell System in the Eye and ENT Hospital of Fudan University were enrolled in this study. Results: A total of 46 newborns (66 ears) with helix adhesion were included. The average onset time of treatment was 4.57 ± 3.63 weeks. The average duration of treatment was 7.40 ± 2.05 weeks. 97.0% ears’ (64/66) immediate results were excellent or good. During long-term follow-up, 95.5% ears achieved excellent or good outcomes. Age of initiation treatment significantly affected immediate (p=0.001) and long-term (p=0.004) outcomes. Conclusions: EarWell System was an effective method to correct auricular helix adhesion. Using this approach, patients with helix adhesion could avoid surgeries. Age of initiation treatment was the predictor of successful correction.